Relevansi Kesetaraan Gender dan Peran Perempuan Bekerja terhadap Kesejahteraan Keluarga di Indonesia (Perspektif Ekonomi Islam) - Putri Dyah Ayu Fitriyaningsih; Fita Nurotul Faizah Munawan (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2020)
This study aims to identify problems related to the relevance of gender equality and the status of working women to family welfare in Indonesia based on an Islamic economic perspective. This study uses descriptive qualitative research methods with secondary data provided is documentation. The results of this study indicates that there is no dichotomy of public space for women and men in work. Both have the same rights and obligations. Islam as a religion rahmatan lil alamin also expressly explains about human freedom to work and cooperate in "amar ma'ruf nahi munkar". In addition, within the scope of statehood in Indonesia, attention to equality of rights and obligations to work is also regulated in Law No. 13 of 2003 concerning employment. Gender equality in this work provides opportunities for women to participate in meeting the family economy. So that it will directly change the source of household income which initially only 1 (one) source, that is husband, becomes 2 (two) sources, namely husband and wife. The establishment of synergy between men and women in the domestic and public sectors, will improve family welfare, both material (financial) and non-material.